Immunolocalization of matrix polysaccharides during wood decay by white rot fungus: evidence for specific interaction between hemicellulose and lignin in the wood fibre cell wall of Dalbergia sissoo Roxb - Sivan, Pramod; Rajput, Kishore S.; Rao, Karumanchi S. (Frontiers in Plant Science, 2026)
Alterations in the structure and chemistry of cell wall polymers during wood decay by white-rot fungi could be one of the best experimental systems to studying the association between different cell wall polymers and the biology of plant-microbe interactions. We investigated the spatial and temporal changes in the distribution patterns of matrix polysaccharides and lignin in the fibre cell walls of D. sissoo wood subjected to preferential delignification and simultaneous decay by two species of white rot fungi. Transmission electron microscopy analysis of fibre walls affected with L. betulina showed removal of lignin from the S1 layer of the secondary walls (SW), resulting in cell separation. Subsequently, preferential removal of lignin from the S2 and S3 layers was observed. The structural changes in the SW of fibres inoculated with D. flavida directly correlated with the simultaneous degradation of all wall polymers. Immunogold labelling-TEM analysis revealed degradation of xyloglucan in the compound middle lamellae (CML) region, undergoing preferential delignification. Weak labelling for less substituted heteroxylans was evident in S2 and S3 layers of preferentially delignified fibre walls. Highly substituted heteroxylans showed a higher distribution in the outer layers of SW even at late stages of degradation. The degradation pattern of cell wall polymers suggests a close association between lignin-heteroxylans in the SW as they were removed simultaneously during preferential delignification in the xylem fibres.